Monoclonal antibody-based localization of major diagnostic antigens in metacestode tissue, excretory/secretory products, and extracellular vesicles of Echinococcus species - Kronenberg, Philipp A.; Reinehr, Michael; Eichenberger, Ramon Marc; Hasler, Sina; Laurimäe, Teivi; Weber, Achim; Deibel, Ansgar; Müllhaupt, Beat; Gottstein, Bruno; Müller, Norbert; Hemphill, Andrew; Deplazes, Peter (Frontiers in Cellular and Infection Microbiology, 2023)
Alveolar (AE) and cystic echinococcosis (CE) are severe parasitic zoonoses caused by the larval stages of Echinococcus multilocularis and E. granulosus sensu lato, respectively. A panel of 7 monoclonal antibodies (mAbs) was selected against major diagnostic epitopes of both species. The binding capacity of the mAbs to Echinococcus spp. excretory/secretory products (ESP) was analyzed by sandwich-ELISA, where mAb Em2G11 and mAb EmG3 detected in vitro extravesicular ESP of both E. multilocularis and E. granulosus s.s. These findings were subsequently confirmed by the detection of circulating ESP in a subset of serum samples from infected hosts including humans. Extracellular vesicles (EVs) were purified, and the binding to mAbs was analyzed by sandwich-ELISA. Transmission electron microscopy (TEM) was used to confirm the binding of mAb EmG3 to EVs from intravesicular fluid of Echinococcus spp. vesicles. The specificity of the mAbs in ELISA corresponded to the immunohistochemical staining (IHC-S) patterns performed on human AE and CE liver sections. Antigenic small particles designated as ‘’spems’’ for E. multilocularis and ‘’spegs’’ for E. granulosus s.l. were stained by the mAb EmG3IgM, mAb EmG3IgG1, mAb AgB, and mAb 2B2, while mAb Em2G11 reacted with spems and mAb Eg2 with spegs only. The laminated layer (LL) of both species was strongly visualized by using mAb EmG3IgM, mAb EmG3IgG1, mAb AgB, and mAb 2B2. The LL was specifically stained by mAb Em2G11 in E. multilocularis and by mAb Eg2 in E. granulosus s.l. In the germinal layer (GL), including the protoscoleces, a wide staining pattern with all structures of both species was observed with mAb EmG3IgG1, mAb EmG3IgM, mAb AgB, mAb 2B2, and mAb Em18. In the GL and protoscoleces, the mAb Eg2 displayed a strong E. granulosus s.l. specific binding, while mAb Em2G11 exhibited a weak granular E. multilocularis specific reaction. The most notable staining pattern in IHC-S was found with mAb Em18, which solely bound to the GL and protoscoleces of Echinococcus species and potentially to primary cells. To conclude, mAbs represent valuable tools for the visualization of major antigens in the most important Echinococcus species, as well as providing insights into parasite-host interactions and pathogenesis.